Analysis of Factors Affecting Rice Farming Production in Ulu Ogan District, OKU District - Sari, Candra; Sari, Yunita; Sari, Fifian Permata (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2022)
Ogan Komering Ulu Regency is a district that has great potential for agricultural businesses, especially rice farming. For rice production in South Sumatra Province, Ogan Komering Ulu district in 2020 occupies the 12th position out of 17 districts/cities, with a total production of 16,807.12 tons of dry milled grain (kg). Ogan Komering Ulu Regency has 13 sub-districts which are rice-producing areas. The Ogan Komering Ulu Regency Government continues to strive to increase the production and productivity of rice commodities in its area. The increase in rice production in Ogan Komering Ulu Regency is not only to meet regional needs but is expected to contribute to increasing national rice production. In 2020 the highest total rice harvested area in Ogan Komering Ulu Regency is in Ulu Ogan District, which is 1,690 ha, with dry milled grain production (kg) of 9,464 tons. So that it can be said, Ulu Ogan District is a food barn for Ogan Komering Ulu Regency. Rice production is the amount of rice obtained at the time of post-harvest. Yield will be affected by land area, fertilizer, and labor. This rise and fall in production results can be caused by several factors that are not precise enough so the production of lowland rice is not optimal. Therefore, there is a need for further analysis related to the factors that influence the production of lowland rice farming in Ulu Ogan District, Ogan Komering Ulu Regency. This study aimed to analyze the factors that influence the production of lowland rice in Ulu Ogan District, Ogan Komering Ulu Regency. This research was conducted in Ulu Ogan District, Ogan Komering Ulu Regency. Sampling in this study was done by a simple random sampling method with 65 farmers as respondents. The variables measured in this study were land area, urea fertilizer, labor, number of seeds, and pesticides. The production model used is the Cobb-Douglas model regression analysis. To see the effect of each production factor on the resulting production using multiple linear regression analysis simultaneously the variables of land area, urea fertilizer, labor, number of seeds, and pesticides affect rice production in Ulu Ogan District, Ogan Komering Ulu Regency. Individually the variables of land area and number of seeds have a significant effect on rice production factors.